The influence of knowledge-based HRM practices on productivity of knowledge workers: A Study on Malaysian universities - Leong, Kai Sheng *; Khairuddin, Sheikh M. H. S.; Tehseen, Shehnaz *; Yan, Yeong Hui * (2019)
Knowledge workers have contributed significantly to the development of nations. There are various researches that extensively recognized the positive impact of knowledge-based HRM practices on knowledge worker's productivity. While there are studies regarding knowledge-based HRM practices across different countries and industries, however, there is dearth of research regarding the impact of knowledge-based HRM practices on universities' knowledge workers. Therefore, the aim of this current study was to fill up the gap by analysing the influence of various knowledge-based HRM practices on the productivity of knowledge workers in universities. This study investigated HRM practices namely knowledge-based recruiting practices, knowledge-based training and development practices, knowledge-based performance appraisal practices and knowledge-based compensation practices on the quality and quantity of the productivity of knowledge workers. Herzberg's Two-Factor Theory, Expectancy Theory, and MacGregor's Theory X and Theory Y were used as underpinning theories to support the proposed conceptual model. Eight hypotheses were developed based on the proposed research model and standard instrument was used to obtain data. By employing non-probability sampling method, a total of 129 knowledge workers in Selangor and Kuala Lumpur participated in survey. The data were collected at one point of time across the sample population. The data obtained were assessed using SPSS and Partial Least Square Structural Equation Modelling (PLS-SEM). Results revealed the positive and significant influence of knowledge-based recruiting practices and knowledge-based compensation practices on quality and quantity of knowledge workers' productivity. Knowledge-based training and development practices were found to have their positive and significant impact on quantity of knowledge workers' productivity but not on quality of knowledge workers' productivity. Additionally, knowledge-based performance appraisal was not found to have its positive as well as significant impact on quality and quantity of knowledge worker's productivity.